Germination of morphology and evaluation of emergency of cambucá (Myrciaria floribunda(H. West ex Willd)O Berg) in substrates - Carvalho Moreira, Francisco José; Tavares, Maria Klécia das Neves; da Silva, Maria Cristina Barbosa; Silva, Karla da Fonseca; Pinheiro Neto, Luís Gonzaga (Revista Brasileira de Engenharia de Biossistemas, 2026)
The germinative aspects of native species plants are important, as they provide useful information for the production and control of forest seedlings, management, as well as taxonomic identification in the field. With the aim of studying the morphology of germination and emergence of cambucá (Myrciaria floribunda) depending on the types of substrates, the experiment was carried out, conducted in Greenhouse at IFCE - campus Sobral, during the period from August 2019 to March 2020. The trial was developed in a completely randomized design (DIC), with six treatments, consisting of the types of substrates, namely (sand, sand + cattle manure, sand + goat manure, cattle manure, goat manure, cattle manure + manure goat), with four replications of 15 seeds each. At 192 days after sowing, the final evaluation of the trial was carried out, measuring: emergence (%), speed index (IVE) and average emergence time (TME), plant height, number of leaves, stem diameter stem, root growth, shoot fresh and dry weight, root fresh and dry weight and the Dickson quality index (DQI). The data were tabulated and analysis of variance was carried out using the F test (p<0.05), using the Assistat Beta 7.7 statistical program, with the treatment means compared using the Tukey test (p<0.05). With the results, it is concluded that cambucá (Myrciaria floribunda) seeds present slow and uneven emergence; The sand substrate is the most suitable for its germination, cambucá seedlings do not develop well in high concentrations of organic matter in the substrate.